Aplikasi Pembelajaran Interaktif Berbasis Adobe Animate Pada Pembelajaran Moral Etika di Sekolah Metta Maitreya - Mega Kartika; Yenny Desnelita (Jurnal Ilmu Komputer dan Sistem Informasi, 2025)
The advancement of information technology has created significant opportunities in the field of education, particularly in the development of interactive learning media. This research aims to design and develop an interactive learning application based on Adobe Animate to support the teaching of Moral Ethics at Metta Maitreya School. The development method employed in this study is the waterfall model, which encompasses stages of needs analysis, system design, implementation, testing, and maintenance. The application is designed to provide a more engaging and interactive learning experience for first-grade elementary students, featuring digital materials, interactive quizzes, and educational games. Testing is conducted using black box testing methods to ensure that each function operates effectively. Additionally, the effectiveness of the application is evaluated through questionnaires distributed to teachers. The results of the testing and evaluation indicate that this application is effective in enhancing students' understanding of Moral Ethics concepts. With an average user satisfaction score of 93.4%, the application is regarded as user-friendly, engaging, and capable of increasing student interaction during learning. In conclusion, this application represents an innovative solution to support technology-based teaching methods, particularly in the area of Moral Ethics education at the elementary school level.